A life together : Lucas Alamán and Mexico, 1792-1853 - Van Young, Eric (Yale University Press, 2021)
"Lucas Alamán (1792-1853) was the most prominent statesman, political economist, and historian in nineteenth-century Mexico. Alamán served as the central ministerial figure in the national government on three occasions, founded the Conservative Party in the wake of the Mexican-American War, and authored the greatest historical work on Mexico's struggle for independence. Though Mexican historiography has painted Alamán as a reactionary, Van Young's balanced portrait draws upon fifteen years of research to argue that Alamán was a conservative modernizer, whose north star was always economic development and political stability as the means of drawing Mexico into the North Atlantic world of advanced nation-states. Van Young illuminates Alamán's contribution to the course of industrialization, advocacy for scientific development, and unerring faith in private property and institutions such as church and army as anchors for social stability, as well as his less commendable views, such as his disdain for popular democracy."--